Autentisitas Akta Notaris yang Dibuat Secara Elektronik pada Masa Pandemi COVID-19 - Kimbal, Lovita Gamelia; Negara, Tunggul Anshari Setia; Susilo, Hariyanto (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
The purpose of this study was to analyze the authenticity of electronic deeds in terms of the Civil Code, Law Number 30 of 2004 in conjunction with Law Number 2 of 2014, and Law Number 19 of 2016 and analyze the urgency of making a notary deed electronically. This study used a normative juridical method with a statutory approach. Prescriptive analytical techniques analyzed primary legal materials and secondary legal materials. The results and discussion showed that the deed made electronically did not meet the exact requirements as stated in Article 1868 of the Civil Code, Article 1 point 7 and Article 16 of Law Number 30 of 2004 in conjunction with Law Number 2 of 2014, and Article 5 paragraph (4) of Law Number 19 of 2016. The urgency of making a notary deed electronically during the COVID-19 pandemic was that there were obstacles for the public to physically attend the notary's office due to physical distancing policies, so notaries were required to innovate in implementing cyber notary related to the making of deeds electronically.